Меdiaspace of Germanic Philology - Pylypenko, R. Ye. (Cognition, Communication, Discourse, 2018)
This article reveals the actual tendencies in the development of German philology mediaspace (GPMS). Its structural features are determined according to the four segments relatively singled out: educational segment as place of capture virtual communication; informational segment as place of retrieval of professional data; interactive segment as working platform of intercourse of philological research community; publishing segment as field of creative self-realization of philologists.